THE INDONESIAN ECONOMY DURING THE JAPANESE OCCUPATION - Thee Kian Wie (Masyarakat Indonesia, 2013)
This article is written as one of many tributes to Professor Anne Booth of theDepartment of Economics, School of Oriental and African Studies (SOAS), Universityof London, who will retire by the end of 2013. This tribute is certainly warranted asAnne Booth is without doubt a redoubtable scholar specialized in the economy andhistory of the Southeast Asian nations, particularly Indonesia. The article starts withdiscussing developments in the Netherlands Indies in the 1930s, which is followedby a discussion of developments in the Netherlands Indies on the eve of the Japaneseinvasion. The article then discusses political developments in Japan in the 1930s;followed by a discussion of the start of the Pacific War and the fall of the NetherlandsIndies. The main focus of the article concerns the Indonesian economy during theJapanese occupation of Indonesia (March 1942 August 1945).Keywords: Japanese Occupation, Indonesian economy, Netherlands Indies